2008
DOI: 10.1021/nn700176a
|View full text |Cite
|
Sign up to set email alerts
|

Lipid−Quantum Dot Bilayer Vesicles Enhance Tumor Cell Uptake and Retention in Vitro and in Vivo

Abstract: We report the construction of lipid-quantum dot (L-QD) bilayer vesicles by incorporation of the smallest (2 nm core size) commercially available CdSe/ZnS QD within zwitterionic dioleoylphosphatidylcholine and cationic 1,2-dioleoyl-3-trimethylammonium-propane lipid bilayers, self-assembling into small unilamellar vesicles. The incorporation of QD in the acyl environment of the lipid bilayer led to significant enhancement of their optical stability during storage and exposure to UV irradiation compared to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 45 publications
6
116
1
Order By: Relevance
“…The liposome-QD hybrids preserve the features of both QDs and liposomes and are compatible with aqueous phase and biological milieu. 181 They can be directly internalized by tumor cells and may be further engineered by altering liposome constituents for in vivo studies. For example, the introduction of cholesterol into the liposome may enhance the in vivo stability of liposome-QD hybrids, the inclusion of a fusogenic lipid may enhance the in vivo diffusion of liposome-QD hybrids, and the coupling of tumor-targeted ligands onto the surface of the liposomes may direct the targeting of liposome-QD hybrids to tumor cells.…”
Section: Functionalization Of Chemically Synthesized Quantummentioning
confidence: 99%
See 1 more Smart Citation
“…The liposome-QD hybrids preserve the features of both QDs and liposomes and are compatible with aqueous phase and biological milieu. 181 They can be directly internalized by tumor cells and may be further engineered by altering liposome constituents for in vivo studies. For example, the introduction of cholesterol into the liposome may enhance the in vivo stability of liposome-QD hybrids, the inclusion of a fusogenic lipid may enhance the in vivo diffusion of liposome-QD hybrids, and the coupling of tumor-targeted ligands onto the surface of the liposomes may direct the targeting of liposome-QD hybrids to tumor cells.…”
Section: Functionalization Of Chemically Synthesized Quantummentioning
confidence: 99%
“…Furthermore, Kostarelos and colleagues constructed a series of liposome-QD hybrids for diagnostic and therapeutic applications. 181,540,542,567,568 Their research reveals that the lipid composition and bilayer characteristics of liposome-QD hybrid vesicles may significantly affect their stability in blood, in vivo pharmacological behavior, and tissue biodistribution profile. 567,568 Brinker and colleague prepared a porous nanoparticle-supported lipid bilayer (protocell) with the features of both liposomes and mesoporous silica nanoparticles (MSNs).…”
Section: Mesoporous Silica/quantum Dot-based Drugmentioning
confidence: 99%
“…Several studies, have demonstrated that the physicochemical properties of different types of nanomaterials, provide a higher dye stability [7,8] and sensitive detection from single-molecule level to human body applications, i.e. from in vitro diagnosis to in vivo real-time imaging [9][10][11]. Consequently, the physicochemical properties of NPs open the possibility to obtain sensitive data in a noninvasive manner, providing a breakthrough in early-stage cancer diagnosis, stem cell tracking, drug delivery, and pathogen detection [12][13][14][15][16][17][18].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT11 3.2. ANALYTICAL DETECTION OF EPEF COMPOUNDSAs mentioned before in the experimental section, EPE was subjected to precipitation reaction by changing pH; with this, it was assured that onlyTable 1.…”
mentioning
confidence: 99%
“…It is an attractive and simple way to form thermodynamically stable bilayers. Major advantage of this approach is the possibility to incorporate the functionalized molecules (proteins, nanoparticles) into the membrane for specific applications [21][22][23]. The thickness of typical SLBs is about 4 up to 6 nm, depending on the lipid composition [24].…”
Section: Introductionmentioning
confidence: 99%